2020
DOI: 10.3390/ijns6020038
|View full text |Cite
|
Sign up to set email alerts
|

National Program for External Quality Assessment of Chinese Newborn Screening Laboratories

Abstract: Objectives: To analyze the coefficient of variation (CV) of external quality assessment (EQA) in Chinese newborn screening (NBS) laboratories. Method: EQA’s robust CV was analyzed by the Clinet-EQA evaluation system. Results: Participating laboratories of the EQA program increased annually. There was more than a 11-fold increase in phenylalanine (Phe) and thyroid stimulating hormone (TSH). It has shown a declining robust CV, which has tended to level off in recent years. The interquartile range (IQR) of Phe an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…There are several recent reports related to expanded NBS with MS/MS: an evaluation of MS/MS implementation in Suqian city (North) [ 447 ]; analyses of the cost effectiveness of ENBS in Shenzhen (South) [ 448 ] and Zhejiang province (East) [ 449 ]; and studies to determine the disease spectrum and genetic characteristics of IEMs detected by ENBS in Xi’an city (Northwest) [ 450 ] and Changsha (Central) [ 451 ]. A robust system-wide quality management system exists including both laboratories (National Center for Clinical Laboratories) [ 452 ] and non-laboratory components [ 453 ], sometimes augmented by regional quality improvement activities [ 454 ]. A large study was reported in 2021 that determined normal ranges for 35 MS/MS conditions in the Chinese newborn population [ 455 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are several recent reports related to expanded NBS with MS/MS: an evaluation of MS/MS implementation in Suqian city (North) [ 447 ]; analyses of the cost effectiveness of ENBS in Shenzhen (South) [ 448 ] and Zhejiang province (East) [ 449 ]; and studies to determine the disease spectrum and genetic characteristics of IEMs detected by ENBS in Xi’an city (Northwest) [ 450 ] and Changsha (Central) [ 451 ]. A robust system-wide quality management system exists including both laboratories (National Center for Clinical Laboratories) [ 452 ] and non-laboratory components [ 453 ], sometimes augmented by regional quality improvement activities [ 454 ]. A large study was reported in 2021 that determined normal ranges for 35 MS/MS conditions in the Chinese newborn population [ 455 ].…”
Section: Resultsmentioning
confidence: 99%
“…To ensure the quality of screening, the National Center of Clinical Laboratory (NCCL) of China requires all NBS laboratories to participate in the Newborn Screening Quality Assurance Program (NSQAP). 4,5 By providing plans for internal quality control (IQC) and external quality assessment (EQA), the NSQAP ensures testing accuracy in all screening laboratories. NBS is a complex system comprising more than only laboratory testing.…”
Section: Introductionmentioning
confidence: 99%
“…However, in mainland China, there are still disputes on the utilization cut-off value for the PKU screening, as different cut-off values are used in various regions. [10][11][12] In this study, we aimed to optimize the cut-off value in Xinjiang Uygur Autonomous Region based on the Phe screening results. Our study contributed to the PKU screening based on the Phe concentration.…”
mentioning
confidence: 99%